Primary Squamous Cell Carcinoma of the Pancreas: A Case Report - Adachi, Kensuke (JOP. Journal of the Pancreas, 2011)
Context Since the pancreas in the normal state is entirely devoid of squamous cells, squamous cell carcinoma of the pancreas is a controversial entity of uncertain origin. Reports of pancreatic carcinomas exhibiting a pure squamous morphology are very rarely described in the English literature. Case report We herein report a case of pure squamous cell carcinoma of the pancreas in a 67-year-old woman. Preoperative imaging studies demonstrated a huge solid tumor which appeared to originate from the retroperitoneum with invasion of both the stomach and the pancreas. Her past medical history was unremarkable. A total gastrectomy with distal pancreatectomy and splenectomy was carried out to remove the tumor. Pathological examination of the resected specimen confirmed a diagnosis of pure, well-differentiated squamous cell carcinoma of the pancreas with invasion of the stomach and regional lymph node metastases. Conclusion On the basis of perioperative and postmortem examinations of the malignancy, we could not detect any other squamous cell carcinoma lesions, such as in the nasopharynx, lung, uterus, vagina, urinary bladder, skin and esophagus which had metastasized to the pancreas. We concluded that this case should be diagnosed as primary squamous cell carcinoma of the pancreas. Image: Submucosal tumor located at the lesser curvature and the posterior wall of the upper gastric body.